Empowering Educational Leadership: The Role of Principal in Enhancing Learning Quality and Teacher Performance - Aimang, Hasrat A; Judijanto, Loso; Mufarrihah, Anik; Suprayitno, Degdo; Susanti, Melly (JURNAL AL-TANZIM, 2024)
This study analyzes how principal leadership can manage their teaching staff to improve the quality of learning and their performance in schools. This study uses a qualitative approach to the case study type. Data collection techniques are carried out through interviews, observations, and documentation. Data analysis uses the Miles and Huberman interactive model, which consists of data reduction, presentation, and conclusion. The study results indicate that effective principal management involves several main stages, namely planning teacher performance development programs, developing clear strategies, and scheduling integrated with the school's academic calendar. Principals who successfully implement this management can consistently improve teacher performance, which improves the quality of learning in schools. In addition, the principal's provision of rewards and sanctions has proven to be an effective motivator for teachers to continue improving their performance. This study is expected to significantly contribute to the literature on educational management by highlighting the importance of the role of the principal in improving the quality of learning through effective management.